Morphological and Chemical Characteristics of Porang Tubers (Amorphophallus oncophyllus) From Different Harvest Periods - Gusti Setiavani; Budi Suarti; Mona Nur Moulia; Aisar Novita; Seca Gandaseca (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University, 2023)
Porang tubers (Amorphophallus oncophyllus) have recently garnered more attention with the increasing demand for their derivative products. This research aimed to determine the morphological and chemical characteristics of porang tubers from different harvest periods. The method used was a completely randomized design. Also, for comparison, the morphological and chemical characteristics of bulbils were obtained from previous studies. Based on the analysis, morphologically, the stem tubers have an oval shape developing at the base of the stem with yellowish-brown to orangish-brown skin. Bulbils have an irregular oval shape with brown skin and white spots. They all have similarly dark yellow fibers. The stem tubers in the first harvest period were smaller in diameter and lighter (479.20 ± 183.54 g) than in the second period (609.71 ± 169.42 g). In contrast, bulbils at the leaf axils are smaller (diameter = 3–3.7 cm, thickness = 1.9–2.4 cm) and only weigh about 12.3–25.3 g. Chemical analysis revealed that the flour made from the stem tubers contained 14.28–17.57% glucomannan and 9.16–11.10% protein, generally higher than bulbils with 25.78% glucomannan and 9.52% protein (very low). The yields of porang flour were 0.15±0.02% and 0.14±0.01% from the first and second harvest.